Evaluation of the School Literacy Movement Program at Sridadi Public Elementary School 1 in Central Lampung Regency - Bernadeta Elsa Gita Saputri; Aman Aman; Era Mutiara; Arif Dwi Suryanto; Albertus Febza Kusuma; Zamzami Zamzami (FKIP - Universitas Riau, 2026)
This study was conducted to provide empirical evidence regarding the effectiveness of the School Literacy Movement (SLM) program in increasing elementary students’ reading interest. The study aimed to evaluate the implementation of the SLM program at SD Negeri 1 Sridadi to develop students’ reading habits and increase their reading interest. This evaluative research employed the CIPP (Context, Input, Process, Product) evaluation model using a mixed-methods approach. Data were collected through document analysis, in-depth interviews with the principal, teachers, and library managers, and questionnaires measuring students’ reading interest. The results indicate positive achievements across all evaluation components. The Context component was categorized as “Very Good,” indicating alignment between program planning and school needs. The Input component was adequate in terms of infrastructure, human resources, funding, and library management, although the availability of non-curricular reading materials remained limited. The Process component was rated “Good,” particularly for implementing a 15-minute reading habit before lessons, though stronger monitoring and evaluation are needed. The Product component showed a “Very Good” level of reading interest and improved reading habits. Overall, the SLM program has been implemented effectively, although improvements in input aspects are still needed.